Adolescent Fertility and Sexual Health in Nigeria - Cortez, Rafael; Saadat, Seemeen; Marinda, Edmore; Odutolu, Oluwole (World Bank, Washington, DC, 2016)
This study examines the determinants of adolescent sexual behavior and fertility in Nigeria, with a special focus on knowledge, attitudes and behaviors of adolescents aged 10-19 years old in Karu Local Government Authority (LGA), a peri-urban area near the capital city of Abuja. Using the last three waves of Demographic and Health Surveys (2003, 2008, 2013), focus group discussions, stakeholder interviews, and a specialized survey of 643 girls and boys aged 10-19 years old in Karu LGA, the study narrows in on key challenges to and opportunities for improving adolescent sexual and reproductive health outcomes. The national median age at sexual debut for adolescent girls and boys is between 15 and 16 years of age. This is closely emulated in Karu LGA with a median age of 14.8 years for girls and 15.3 years for boys. While data on pregnancies was limited in the Karu sample, DHS data show that for girls, sexual debut is closely associated with marriage or cohabitation, which in turn is a strong predictor of adolescent fertility. Poverty is another strong predictor, with the odds of becoming pregnant being twice as high for adolescents in the lower wealth quintiles compared to their counterparts in the richest quintile in the country. While adolescents’ knowledge of contraception has increased from under 10 percent to over 30 percent, use of health services among adolescents for SRH (and contraception) is limited due to factors such as fear of stigma, embarrassment, and poor access to services, something also emphasized in focus group discussions. Challenges for improving adolescent SRH outcomes relate to: (i) the paucity of data, especially on the 10-14 year olds; (ii) availability and access to youth-friendly services and the Family Life and HIV Education (FLHE); (iii) reaching out-of-school adolescents with SRH information; and (iv) addressing ambiguities and gaps in Federal law and customs on age at marriage, and generating support for the legal age at marriage of at least 18 years old. Addressing these barriers at the State and sub-regional levels is going to be critical in improving adolescent well-being.